Insights on financial services regulation - Consiglio, John A. (Bingley, U.K. : Emerald Publishing Limited, 2020)
The debates around financial services regulation are fierce and unending, and with every new development or law, rigid positions seem to grow. In this insightful new book, expert author John A. Consiglio discusses developments in this vital part of the wide world of finance. Including discussions on the public interest elements of regulation, on informational asymmetry, and on the economist/regulator duopoly, Consiglio analyses various key contentious element of regulatory practices from both the regulators' and regulatees' perspectives. Focusing on the chasm between the perceived hierarchical aloofness of regulators, and the real needs of individual users of financial services, Consiglio explores the complicated and often worrying landscape of financial services regulation. Looking across historical detail to the present, and future, of regulation, the chapters also include a keen discussion of economics and regulatory pedagogy in the modern age. For researchers and students of finance, and for all professionals involved in the financial services sector, this is an unmissable book that interrogates the current landscape defining our global economy.
Includes bibliographical references and index.
Print version record.
Keywords: Financial services industry -- Law and legislation; Banking law; Business & Economics -- Finance -- General; Finance